Application of the three-point bending test for small-sized wood and veneer samples. Issue 3 (4th May 2022) - Siegel, Carolin; Buchelt, Beate; Wagenführ, André
ABSTRACT: The aim of this work is to establish a bending test method as evaluation criteria for mechanical properties (strength and modulus of elasticity) of veneers. The bending test is one essential and easy test method for wood characterization. Actually there are no established methods for characterizing smaller sized wood samples – in particular veneer. This investigation is based on the established test methods for solid wood. The three-point bending test was successfully conducted with veneer and small-sized samples and evaluated.